2010
DOI: 10.1007/s10554-010-9704-2
|View full text |Cite
|
Sign up to set email alerts
|

Midregional pro-atrial natriuretic peptide: a novel marker of myocardial fibrosis in patients with hypertrophic cardiomyopathy

Abstract: We aimed to determine the diagnostic performance of biomarkers in predicting myocardial fibrosis assessed by late gadolinium enhancement (LGE) cardiovascular magnetic resonance imaging (CMR) in patients with hypertrophic cardiomyopathy (HCM). LGE CMR was performed in 40 consecutive patients with HCM. Left and right ventricular parameters, as well as the extent of LGE were determined and correlated to the plasma levels of midregional pro-atrial natriuretic peptide (MR-proANP), midregional pro-adrenomedullin (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(65 reference statements)
1
7
0
2
Order By: Relevance
“…However, Briguori et al 18 reported that plasma concentration of ANP in HCM was strongly associated with left atrial function, whereas BNP was strongly associated with obstruction. Only one study, including only 40 patients, has investigated MR-proANP in patients with HCM, showing that among several biomarkers, MR-proANP was the only one associated with the extent of late gadolinium enhancement on MRI 26. As previous studies, we found a significant association between NYHA and natriuretic peptides although there was a significant overlap between NYHA 2 and 3–4 (figure 1).…”
Section: Discussionsupporting
confidence: 72%
“…However, Briguori et al 18 reported that plasma concentration of ANP in HCM was strongly associated with left atrial function, whereas BNP was strongly associated with obstruction. Only one study, including only 40 patients, has investigated MR-proANP in patients with HCM, showing that among several biomarkers, MR-proANP was the only one associated with the extent of late gadolinium enhancement on MRI 26. As previous studies, we found a significant association between NYHA and natriuretic peptides although there was a significant overlap between NYHA 2 and 3–4 (figure 1).…”
Section: Discussionsupporting
confidence: 72%
“…The specificity, positive and negative predictive value were satisfying. The results imply that MR-proANP is a potential biomarker of myocardial fibrosis in patients with HCM [63].…”
Section: Other Biomarkersmentioning
confidence: 74%
“…A recent metaanalysis has shown that measurement of copeptin levels in addition to Tn improves the sensitivity and negative likelihood ratio for diagnosis of acute MI compared with Tn alone. 29 33 They did not find a relation between copeptin levels and degree of cardiac fibrosis in HCM. They found that LV and LA diameters and IVS thickness were higher in patients with cardiac fibrosis, but they did not classify patients as obstructive and nonobstructive HCM.…”
Section: Discussionmentioning
confidence: 90%
“…They found that copeptin levels increased significantly 30 minutes after induction of MI and peaked at 90 minutes. Elmas et al assessed the correlation of various biochemical parameters, including copeptin, with cardiac fibrosis detected by magnetic resonance imaging in 40 patients with HCM . They did not find a relation between copeptin levels and degree of cardiac fibrosis in HCM.…”
Section: Discussionmentioning
confidence: 99%